BOŽANSTVA MODERNITETA - CHITTICK, William C.; Dubravac, Haris (Novi Muallim, 2017)
UDK 28-17 Iz djela: William C. Chittick, Science of the Cosmos, Science of the Soul: The Pertinence of Islamic Cosmology in the Modern World, Oneworld Publications, Oxford, 2007., pp. 12–22.